Exploration of Knowledge and Community Preparedness in Flood Disaster Mitigation - Erman Syarif; M. Maddatuang; H. Hasriyanti; Alief Saputro (Geosfera Indonesia, 2022)
Floods are natural disasters that should be highly considered due to their threats to human lives and the economy. It is also the third largest natural disaster in the world, which has claimed many lives and properties. Therefore, this study aims to identify community knowledge about floods and determine the efforts to increase preparedness strategies. A qualitative study was conducted in the village of Sapanan, Binamu District, Jeneponto Regency, Indonesia. Subsequently, data collection was carried out by observation, interviews, and documentation with various selected informants. Based on the results, the following were obtained, 1) The level of knowledge and actions performed by the Sapanan people was quite good regarding flooding. This was due to the experience of the community with the disaster, which they had decided to use as a learning platform, 2) The impacts often caused after flooding were the outbreaks of many diseases, which hindered the community from performing their usual activities. This was because they were busy cleaning their homes, with children consequently unable to attend school regarding the muddy state of the chairs and environment, and 3) The community's efforts to increase preparedness for the disasters included land use monitoring and prone location planning in safe areas. In this case, the level of knowledge and actions performed by the people of Sapanan village was quite good concerning flooding. This was because of their numerous experience with the disaster, which they had decided to use as a learning platform. Keywords : knowledge; preparedness; the community; flood Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License